OUTREACHES CONTENT TRACING TECHNIQUE FOR SOCIAL NETWORKING SERVICES - Molodetska-Hrynchuk, K. (Radio Electronics, Computer Science, Control, 2017)
Context. Today’s social networking services have turned into an efficient communication tool for the members of virtual communities termed actors. The high rate of content dissemination, transboundary interactions between the actors and the drives to group the latter up, could make the services efficient cyberwarfare against the person, society and country. Text content is the most frequently used means of communication between the actors of virtual communities. The actual theoretical and applied research, aimed at designing maintenance procedures for the national cybersecurity system, is to solve the problem of text content monitoring. Objective. The research objective is to suggest and design a method for detecting outreaches by their content in the collection of text to solve the problem of efficient monitoring the social media. Method. The method designed is based on the modern content analysis approaches, i. e. the latent semantic indexing and the semantic analysis based on ontology. Results. The latent semantic indexing selects the concept relevant context by its content ignoring key word density. The semantic analysis will specify the further techniques of detecting harmful semantic structures in the body of text selected. When any conceptual mismatches in the text content and ontology detected and professionally analyzed, the ontology knowledge bases get updates of the social networking service cyberthreat patterns. Thus, the combination of both produces cancelling effect on the defects of and uncovers latent relationships between linguistic units. Conclusions. The outreaches tracing method proactively identifies cyberwarfare in virtual communities waged against individual, social and national cybersecurity. The suggested method increases efficiency and effectiveness of the national cybersecurity system on social networking services.